Wogonin Attenuates Hippocampal Neuronal Loss and Cognitive Dysfunction in Trimethyltin-Intoxicated Rats - Lee, Bombi (Biomol Ther (Seoul), 2016)
We examined whether wogonin (WO) improved hippocampal neuronal activity, behavioral alterations and cognitive impairment, in rats induced by administration of trimethyltin (TMT), an organotin compound that is neurotoxic to these animals. The ability of WO to improve cognitive efficacy in the TMT-induced neurodegenerative rats was investigated using a passive avoidance test, and the Morris water maze test, and using immunohistochemistry to detect components of the acetylcholinergic system, brain-derived neurotrophic factor (BDNF), and cAMP-response element-binding protein (CREB) expression. Rats injected with TMT showed impairments in learning and memory and daily administration of WO improved memory function, and reduced aggressive behavior. Administration of WO significantly alleviated the TMT-induced loss of cholinergic immunoreactivity and restored the hippocampal expression levels of BDNF and CREB proteins and their encoding mRNAs to normal levels. These findings suggest that WO might be useful as a new therapy for treatment of various neurodegenerative diseases.